2010
DOI: 10.1186/1758-2652-13-33
|View full text |Cite
|
Sign up to set email alerts
|

Association between HIV replication and serum leptin levels: an observational study of a cohort of HIV‐1‐infected South African women

Abstract: BackgroundAdvanced HIV infection can result in lipoatrophy and wasting, even in the absence of ongoing opportunistic infections, suggesting that HIV may directly affect adipose tissue amount and distribution.MethodsWe assessed the relationship of fat (measured using anthropometry, DEXA, MRI scans) or markers related to glucose and lipid metabolism with viral load in a cross-sectional sample of 83 antiretroviral-naïve HIV-1-infected South African women. A multivariable linear model was fitted to log10VL to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
10
2
Order By: Relevance
“…6 Our observations do not support this association, but the two cohorts are not similar, as our patients were on stable cART for more than 6 months. Leptin may have important immune functions and in HIVinfected patients may be positively correlated to CD4+ T lymphocytes count.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…6 Our observations do not support this association, but the two cohorts are not similar, as our patients were on stable cART for more than 6 months. Leptin may have important immune functions and in HIVinfected patients may be positively correlated to CD4+ T lymphocytes count.…”
Section: Discussioncontrasting
confidence: 63%
“…5,6 The serum leptin level was lower in HIV patients with a lower CD4 count. 5 Leptin levels may also be inversely correlated to HIV replication, independent of the amount of adipose tissue or disease progression.…”
mentioning
confidence: 98%
“…Interestingly, GBV-C coinfection appeared to restore leptin levels in HIV-1-infected patients (Figure 1). A negative correlation between HIV-1 load and leptin concentration has been previously reported [26], suggesting that this cytokine may affect HIV-1 replication. No correlation was found in this study between HIV-1 load and leptin levels, neither in HIV-1-infected patients, nor in GBV-C co-infected patients (data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…Azzoni et al in 2010 observed that serum leptin levels are inversely associated with HIV replication, independent of disease progression. In the same study, the authors reported a weak association between leptin levels and the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) [39]. Mynarcik et al (2002) found that levels of leptin did not correlate with insulin sensitivity, in HIV-infected subjects with body fat redistribution [37].…”
Section: Resultsmentioning
confidence: 99%